A novel placental tissue biologic, PTP-001, inhibits inflammatory and catabolic responses in vitro and prevents pain and cartilage degeneration in a rat model of osteoarthritis. Issue 8 (August 2021) - Flannery, C.R.; Seaman, S.A.; Buddin, K.E.; Nasert, M.A.; Semler, E.J.; Kelley, K.L.; Long, M.; Favret, J.; Pavesio, A.; Loeser, R.F.
Summary: Objective: Characterization of a novel human placental tissue-derived biologic, PTP-001, which is in development as a candidate therapeutic for the treatment of osteoarthritis symptoms and pathophysiology. Methods: Human placental tissues from healthy donors were prepared as a particulate formulation, PTP-001. PTP-001 extracts were assayed for the presence of disease-relevant biofactors which could have beneficial effects in treating osteoarthritis. PTP-001 eluates were tested in human chondrocyte cultures to determine effects on the production of a key collagen-degrading matrix metalloproteinase, MMP-13. PTP-001 eluates were also assessed for anti-inflammatory potential in human monocyte/macrophage cultures, as well as for growth-stimulating anabolic effects in human synoviocytes. The in vivo effects of PTP-001 on joint pain and histopathology were evaluated in a rat model of osteoarthritis induced surgically by destabilization of the medial meniscus. Results: PTP-001 was found to contain an array of beneficial growth factors, cytokines and anti-inflammatory molecules. PTP-001 eluates dose-dependently inhibited the production of chondrocyte MMP-13, and the secretion of proinflammatory cytokines from monocyte/macrophage cultures. PTP-001 eluates also promoted proliferation of cultured synovial cells. In a rat osteoarthritis model, PTP-001 significantly reduced pain responses throughout 6 weeks post-dosing. The magnitude and duration of pain reduction following a single intraarticular treatment with PTP-001 was comparable to that observed for animals treated with a corticosteroid (active control). For rats dosed twice with PTP-001, significant reductions in cartilage histopathology scores were observed. Conclusions: PTP-001 represents a promising biologic treatment for osteoarthritis, with a multi-modal mechanism of action that may contribute to symptom management and disease modification.